A Human iPSC Line Carrying a de novo Pathogenic FUS Mutation Identified in a Patient With Juvenile ALS Differentiated Into Motor Neurons With Pathological Characteristics - Chen, Li; Wang, Yali; Xie, Jie (Frontiers in Cellular Neuroscience, 2020)
Human-induced pluripotent stem cells (hiPSCs) are used to establish patient-specific cell lines and are ideal models to mirror the pathological features of diseases and investigate their underlying mechanisms in vitro, especially for rare genic diseases. Here, a de novo mutation c.1509dupA (p.R503fs) in FUS was detected in a patient with sporadic juvenile amyotrophic lateral sclerosis (JALS). JALS is a rare and severe form of ALS with unclear pathogenesis and no effective cure. An induced pluripotent stem cell (iPSC) line carrying the de novo mutation was established, and represents a good tool to study JALS pathogenesis and gene therapy strategies for the treatment of this condition. The established human iPSC line carrying the de novo FUS mutation strongly expressed pluripotency markers and could be differentiated into three embryonic germ layers with no gross chromosomal aberrations. Furthermore, the iPSCs could be successfully differentiated into motor neurons exhibiting the pathological characteristics of ALS. Our results indicate that this line may be useful for uncovering the pathogenesis of sporadic JALS and screen for drugs to treat this disorder.